(untitled) (International Journal of Food and Nutritional Sciences, 2023)
This study has provided invaluable insights into the multifaceted applications and significant economic implications of state-of-the-art technologies. A thorough analysis of various application domains has clearly established the substantial potential of machine learning and blockchain technologies in boosting operational efficiency, strengthening security measures, and encouraging innovation within cloud-based environments. The concrete economic impact, seen through cost reductions, revenue growth, and resource optimization, highlights their capacity to bring about transformative changes across a wide range of industries, particularly in the financial and healthcare sectors. This investigation emphasizes the crucial role of technology adoption in shaping the direction of cloud computing and the broader economic landscape. It facilitates well-informed decision-making and strategic planning in the digital era.During the pivotal year of 2022, characterized by remarkable innovation and substantial investments in Applied AI and Cloud Computing, there was a proliferation of cloud services catering to both individual users and businesses.